E-Commerce and Cyber Vulnerabilities in Bangladesh: A Policy Paper - Islam, Muhammad Tanbirul; Islam, Md Fokhrul; Sawda, Juairiya (NAJAHA, 2022)
The e-commerce growth scenario is forging a new dynamism in business and does not offer time-bound, cost-effective and hassle-free buying and selling. Following the changing approach, security management in e-commerce (cyber security) is now a focus. This research is a qualitative research that uses a case study method to analyze risks and vulnerabilities in the field. People in Bangladesh are primarily unaware of the risks related to using computing and digital devices and online platforms. This article articulates the risk factors associated with the growing reliance on digital technologies and devices. Then, some policy guidelines are prescribed for the national level and individual level, including leading social campaigns, new chapters in the school curriculum, advancing technological aptitudes of law enforcers, strengthening security systems in e-commerce, embanking sites, bringing frauds to justice, initiating law to define cybercrimes, fortifying institutional management of cyber securities.